Estudio sobre el barrido de vías públicas en la ciudad de Moyobamba - Pérez Fernández, Jhon Luis (2012)
The present research project referred to as a profile of the thesis entitled "STUDY ON THE SWEEP OF PUBLIC ROADS IN THE MOYOBAMBA CITY 2011" is basically the study of the current situation of the municipal entire wiper system solid waste that is provided in the Moyobamba city, likewise to be able to have a royal diagnosis on the deficiencies as for the service that offers the management and simultaneously be able to present a list of measures that allows to improve significantly the service. Likewise with the execution of the project in mention it allowed to raise technical information in what it recounts tci: total length of paved roads in the Moyobamba city is 19.659 linear meters (19.6 km). The sweep service that is executed in our city; considered basically the Moyobamba urban part the same that amounts to 11.082 linear meters, which in percentage terms represents a 56.4 per cent of people who enjoy the sweep service; the average yield of each worker snowplow is 852.51 mt /snowplow/day, aprox. 0,852 Km 1 snowplow /day. Solid Waste production is of 47.52 metric tons per day that produces our Moyobamba city. The collection type is conventional and semi conventional, the method is of sidewalks and street corners, and to finish the trace collection that is running in the Moyobamba city is double comb and comb. With the implementation of the present thesis draft we are contributing significantly to strengthen environmental management of our province, and for this reason it is of the utmost importance to have a correct management of the entire system of Solid Waste Management in the Moyobamba city. Key words: sweep service, collection type.